2013
DOI: 10.1590/s1519-69842013000300008
|View full text |Cite
|
Sign up to set email alerts
|

The orchid-bee fauna (Hymenoptera: Apidae) of ‘RPPN Feliciano Miguel Abdala’ revisited: relevant changes in community composition

Abstract: The orchid-bee fauna of 'Reserva Particular do Patrimônio Natural Feliciano Miguel Abdala', a 957-ha preserve of Atlantic Forest in eastern Minas Gerais, southeastern Brazil, was surveyed 12 years after the first inventory in the area. Orchid-bee males were actively collected with insect nets when attracted to seventeen chemical compounds used as scent baits. Three hundred and nineteen males belonging to nine species were collected during 40 hours in late December, 2011, when orchid bees are supposedly more ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Roubik (2004a) had already suggested that surveys of orchid-bee males with scent baits during a single day have great utility, and may reveal almost as much about local community structure as studies lasting a full year. The protocol proposed by Nemésio (2010b) has already been used in more than twenty areas in northeastern Brazil (Nemésio, 2010b; this study), southern Bahia (Nemésio, 2011a(Nemésio, , 2013a, northern Espírito Santo (Nemésio, 2011b(Nemésio, , 2013b, Minas Gerais (Nemésio, 2012c;Nemésio and Paula, 2013), and the Peruvian Amazon (Nemésio et al, 2014), always with a high number of collected specimens during a relatively short period of time. With more than 3,000 bees collected in only ten days, the present study revealed one of the highest abundances ever recorded with this 20-hour sampling strategy, only rivalled by the regions of Monte Pascoal, in southern Bahia (Nemésio, 2013d), and Linhares, in northern Espírito Santo (Nemésio, 2013b).…”
Section: Sampling Protocolmentioning
confidence: 89%
“…Roubik (2004a) had already suggested that surveys of orchid-bee males with scent baits during a single day have great utility, and may reveal almost as much about local community structure as studies lasting a full year. The protocol proposed by Nemésio (2010b) has already been used in more than twenty areas in northeastern Brazil (Nemésio, 2010b; this study), southern Bahia (Nemésio, 2011a(Nemésio, , 2013a, northern Espírito Santo (Nemésio, 2011b(Nemésio, , 2013b, Minas Gerais (Nemésio, 2012c;Nemésio and Paula, 2013), and the Peruvian Amazon (Nemésio et al, 2014), always with a high number of collected specimens during a relatively short period of time. With more than 3,000 bees collected in only ten days, the present study revealed one of the highest abundances ever recorded with this 20-hour sampling strategy, only rivalled by the regions of Monte Pascoal, in southern Bahia (Nemésio, 2013d), and Linhares, in northern Espírito Santo (Nemésio, 2013b).…”
Section: Sampling Protocolmentioning
confidence: 89%
“…More important, once sampled, these areas are usually not sampled again so we do not know whether the seasonal pattern observed represents an annual trend of orchid-bee communities at those sites. Only recently, some areas have been re-sampled, with some strikingly different results-but obtained under different sampling protocols (see Nemésio 2013b;Nemésio and Paula 2013).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies in the Neotropics suggest that the main drivers of pollinator decline are deforestation and climate change (e.g. Frankie et al, 2009;Nem esio, 2010aNem esio, , 2013bGiannini et al, 2012;Nem esio et al, 2012;Martins et al, 2013Martins et al, , 2015Nem esio & Paula, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, more than 230 orchid bee species (Hymenoptera: Apidae: Euglossina) are recognised (Nem esio & Rasmussen, 2011) and their communities are richer and most diverse in humid Neotropical forests (Nem esio & Silveira, 2007). Some forest-dependent animal groups, such as the Neotropical orchid bees, may be facing population declines and even local extinctions, especially in the highly fragmented Atlantic Forest of eastern Brazil (Morato, 1994;Tonhasca et al, 2002;Nem esio & Silveira, 2006;Nem esio, 2010aNem esio, , 2011bNem esio, , 2013bNem esio & Paula, 2013). These bees are known to visit orchids and other flowers (reviewed by Dressler, 1982) for aromatic fragrances (Vogel, 1966) supposedly used in courtship behaviour (Eltz et al, 1999).…”
Section: Introductionmentioning
confidence: 99%